2013
DOI: 10.1038/ejcn.2013.163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a carbohydrate-containing late-evening snack on energy metabolism and fasting substrate utilization in adults with acute-on-chronic liver failure due to Hepatitis B

Abstract: A carbohydrate-predominant LES is associated with increases in fasting carbohydrate oxidation, REE and reductions in fat oxidation in adults with ACLF. Therapeutic strategies utilizing LES may promote improved nutritional status in adults with ACLF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Some reports found that carbohydrate-predominant LES promote improved nutritional status [ 108 , 109 ]. Others reported that LES with BCAA were useful in improving protein metabolism and lipolysis in cirrhotic patients and that energy efficiency of BCAA is higher than that of glucose or carbohydrates [ 31 , 106 , 107 ].…”
Section: Nutritional Therapy Before Liver Transplantationmentioning
confidence: 99%
See 4 more Smart Citations
“…Some reports found that carbohydrate-predominant LES promote improved nutritional status [ 108 , 109 ]. Others reported that LES with BCAA were useful in improving protein metabolism and lipolysis in cirrhotic patients and that energy efficiency of BCAA is higher than that of glucose or carbohydrates [ 31 , 106 , 107 ].…”
Section: Nutritional Therapy Before Liver Transplantationmentioning
confidence: 99%
“…The majority of the published studies reported a significant increase in dietary intake when the patients were followed after liver transplantation. These changes are particularly evident in those patients following severe dietary restrictions or in those suffering from relevant gastrointestinal symptoms or anorexia before LT [ 107 , 108 ]. Calories reportedly improved from a median of 27 kcal/kg/day to 32 kcal/kg/day and proteins from a median of 0.8 g/kg/day to 1.3 g/kg/day (comparing dietary intake before LT and 12 months post-transplant [ 73 ].…”
Section: Nutritional Support After Ltmentioning
confidence: 99%
See 3 more Smart Citations